EPIDURAL CORTICOSTEROID INJECTION IN THE MANAGEMENT OF LUMBAR DISC HERNIATION - Dessy R Emril; Novina Rahmati (Jurnal Sinaps, 2021)
Low back pain (LBP) is commonly found in daily practice and a major cause of disability in the world. The most common cause of LBP is herniated disc. Various therapeutic modalities can be an option in the management of LBP caused by herniated disc including conservative therapy, epidural corticosteroid injection, and surgery. In patients who do not respond to conservative therapy and do not meet the criteria for surgery, the only therapy recommended for the patient is epidural corticosteroid injection. Epidural corticosteroid injection has significant effectiveness in reducing pain, restoring function, and reducing the risk for surgery.